Kritični spoprijem s konceptom otrokocentričnosti - Pahor, Sara (Sodobna pedagogika, 2025)
In the article we analyze selected set of texts from the collection Generaciji navidezne svobode: otroci in starši v sodobni družbi (2017), which from the perspective of socio-reproductive mechanisms critically question the educational concept of child-centeredness, as it significantly influences the family upbringing of new generations of children. We are interested in which educational dimensions the criticism is aimed at. In places where, based on the analysis, we find that the concept of child-centerdness and its criticism lack coherent substantiation, we provide additional reflections. We demonstrate that the concept of child-centeredness significantly marks the semantic field of the prevailing ideological production and leads to the upbringing of individuals who, with their personality structure and acquired functional requisites of society restore and maintain dominant social relations.
Keywords: concept of child-centeredness; consumer society; družinska vzgoja; education; family upbringing; ideological speech; ideološki govor; pathological narcissism; patološki narcisizem; pedagogika; pedagogy; potrošniška družba; vzgoja in izobraževanje; zasnova otrokocentričnosti